Penerapan Metode Diskusi Kelompok untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPS di Kelas IX SMP Santa Maria Monica, Bekasi Timur - Ch. Catur Putriyanti; Fabianus Fensi (Universitas Bunda Mulia, 2017)
Learning process and student learning outcomes have a close relationship. A good learning process improves student learning outcomes. Improvement of student learning outcomes is determined by how the learning process is done by teachers. Talking about the learning process is the same as talking about learning and teaching methods. There are many methods of teaching and learning. The teachers and students live to have the method which is in accordance with the conditions of each class. This research tries one of interactive teaching and learning method, that is group discussion. With group discussions the students are invited to discuss lesson themes in social science subjects. To measure the increase of student learning outcomes with this group discussion method then conducted Pre Test about the students' knowledge before the learning process. After the group discussion intervention the teacher performed a Post Test. The result can be said that the teaching and learning methods with group discussion effectively to improve student learning outcomes. Keywords: Learning Method, Group Discussion, Pre Test, Post Test